The contributions of socio-environmental information maps in an environmental mobilisation: the case of a fight against a highway project in France. Issue 9 (2nd September 2022) - Bourgeois, Marc; Sahraoui, Yohan; Dietrich, Judicaelle
ABSTRACT: Large linear transport infrastructure projects, such as highways connecting large metropolitan areas, are continuously under development in France. Although the economic and social benefits of such projects are often disputed, their impacts on the environment and local populations are multiple. These potential impacts almost systematically result in conflicts between decision-makers and planners on one side, and local actors with various profiles (e.g. farmers, residents, environmental associations) mobilised against the projects on the other. In the context of a citizen mobilisation against the A45 highway project in eastern France, this study aimed to analyse the social contributions of maps in terms of information reception. The study is based on the creation of maps representing combined spatial impacts (on mobility, housing, land, landscapes, agriculture, and ecosystems). These maps, created by researchers, were presented in the form of posters aimed at opening discussions with non-experts. The maps created an original medium for discussing and debating the impacts of a highway project through the participatory encounter. Under the lens of spatial and environmental justice, this study questions the discrepancies between who makes decisions on a project and who suffers its impacts, and also raises questions about the position of scientific research in citizen mobilisation.